Bank Syariah Indonesia Share Price Prediction Using Fuzzy Time Series Model Lee Method - Luqmanul Hakiem Ajuna; Hendra H. Dukalang; Muhammad Ardi (Jurnal Madania)
In a forecasting using historical data available in the field there is often a violation of the assumptions required by each method. So that in forecasting there are often obstacles in the fulfillment of these assumptions. Because the forecasting method with the Fuzzy Time Series (FTS) method is a solution to do forecasting without requiring data assumptions. The purpose of this study is to find out how the results of the prediction of the highest stock price of Bank Syariah Indonesia by using the FTS method lee model. This research uses the highest price value of Bank Syariah Indonesia shares, and the data analysis technique used in this study is descriptive statistical analysis Based on the results of research conducted obtained the results of the highest price prediction of Bank Syariah Indonesia daily shares for the next period is as of July 21, 2021 is $2,492.67 per share, and the fuzzy time series error rate using MAPE is 2.28263%.